2023
DOI: 10.1111/liv.15585
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences of authors of major Hepatology society guidelines during the past 15 years

Abstract: Background and Objective: Recent studies have shown that women are underrepresented as authors of medical research and clinical practice guidelines. This study aimed to evaluate gender disparities of authors of major hepatology guidelines. Methods: We reviewed the hepatology guidelines published by the following major gastroenterology societies from January 2008 to September 2022: the American Gastroenterological Association (AGA), American College of Gastroenterology (ACG), American Association for the Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous reports have shown that women senior authors are more likely than men to be associated with women first authors. 16,17 This association was not observed in the study by Tang et al, 15 who instead show that while women senior authors are more likely to work with more women authors in general, the gender of the senior author was not associated with that of the first author, the total number of authors, nor with the number of men authors. Strikingly, between 2009 and 2014, not a single CPG was published with a woman as the first author, and in the three following years, there were only 3 CPGs with a woman as the first author of 25 published CPGs.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Previous reports have shown that women senior authors are more likely than men to be associated with women first authors. 16,17 This association was not observed in the study by Tang et al, 15 who instead show that while women senior authors are more likely to work with more women authors in general, the gender of the senior author was not associated with that of the first author, the total number of authors, nor with the number of men authors. Strikingly, between 2009 and 2014, not a single CPG was published with a woman as the first author, and in the three following years, there were only 3 CPGs with a woman as the first author of 25 published CPGs.…”
mentioning
confidence: 70%
“…The societies also strive to foster the next generations of clinicians and scientists. The proportions of women authors of society-issued CPGs increased significantly during recent years, 15 but several societies had no women first authors, and authorship representation was not proportional to society gender demographics. A true meritocracy is only possible without bias, and science and medicine would thus both be well-served by eliminating gender bias.…”
Section: Ack N O Wle D G E M Entsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, one reported authorship trends in both clinical trials and clinical practice guidelines [39], while more than 15 studies exclusively reported authorship trends in clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53] and 14 reported authorship trends in clinical practice guidelines [54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Study Characteristicsmentioning
confidence: 99%